The compassionate doctor is the best “medicine” for the patient - Paico-Vílchez, Emiliano (2020)
The reflections made by the author are paradigmatically sufficient to point out the following: The compassionate medic achieves a significantly greater healing effect than when he does not practice the feeling of compassion. The compassionate doctor is the best “medicine” for the patient, because he benefits from the optimal results in his health; also, with the experience of satisfaction of having been treated with affection, solidarity, respect, humility, sincerity, honesty, understanding and compassion; that is, to be treated in a humane spirit. Acting the doctor with compassion also benefits himself, as he provides effective and more diligent medical care, has more credibility, improves the doctor-patient relationship, has less exhaustion and avoids incurring malpractice.